2008
DOI: 10.1021/ja800020w
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, Mechanistic, and Computational Investigations of Nitrile-Alkyne Cross-Metathesis

Abstract: The terminal nitride complexes NW(OC(CF 3) 2Me) 3(DME) ( 1-DME), [Li(DME) 2][NW(OC(CF 3) 2Me) 4] ( 2), and [NW(OCMe 2CF 3) 3] 3 ( 3) were prepared in good yield by salt elimination from [NWCl 3] 4. X-ray structures revealed that 1-DME and 2 are monomeric in the solid state. All three complexes catalyze the cross-metathesis of 3-hexyne with assorted nitriles to form propionitrile and the corresponding alkyne. Propylidyne and substituted benzylidyne complexes RCW(OC(CF 3) 2Me) 3 were isolated in good yield upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 47 publications
0
68
0
2
Order By: Relevance
“…Inspired both by a report of Johnson and co-workers, who found that molybdenum and tungsten nitride complexes 24 with fluorinated alkoxide ligands react with alkynes to generate the corresponding metal alkylidynes 25 in situ (Scheme 6) [8081], and by the work of Chiu et al on the preparation of a silanolate-supported molybdenum-nitride complex [82], Fürstner’s group introduced a novel user-friendly catalyst system for alkyne metathesis by employing triphenylsilanol (Ph 3 SiOH) [8384]. Two synthetic routes were developed, which are shown in Scheme 7.…”
Section: Reviewmentioning
confidence: 99%
“…Inspired both by a report of Johnson and co-workers, who found that molybdenum and tungsten nitride complexes 24 with fluorinated alkoxide ligands react with alkynes to generate the corresponding metal alkylidynes 25 in situ (Scheme 6) [8081], and by the work of Chiu et al on the preparation of a silanolate-supported molybdenum-nitride complex [82], Fürstner’s group introduced a novel user-friendly catalyst system for alkyne metathesis by employing triphenylsilanol (Ph 3 SiOH) [8384]. Two synthetic routes were developed, which are shown in Scheme 7.…”
Section: Reviewmentioning
confidence: 99%
“…Recently, we proposed that a trianionic pincer ligand may provide the appropriate ligand arrangement for a reactive AM or NACM catalyst [25]. Trianionic pincer ligands [26e28] bind in the meridional plane of a metal ion [26,29,30], and thus eliminate any thermal barrier to obtaining the T-shaped pendant ligand arrangement proposed for metallocyclobutadiene transition states [12,31]. The difficulty thus far is metalating a trianionic pincer ligand while retaining the MhCR fragment.…”
Section: Introductionmentioning
confidence: 99%
“…Bis(4-methoxyphenyl)acetylene [24,25], VCl 3 (thf) 3 [26], N^Mo(OCMe 3 ) 3 (6) [27], N^Mo(OCMe(CF 3 ) 2 ) 3 (1) [28], and N^Mo(OC(CF 3 ) 3 ) 3 (NCMe) (2) [28], were prepared according to literature procedures. Mesitylene, diphenylacetylene, and chlorotitanium tri-isopropoxide were obtained from Acros.…”
Section: Methodsmentioning
confidence: 99%